Volatile Organic Compound Adsorption by Natural Materials - Azli, Nurul Syafiqah; Nor Haslina Binti Hashim (Progress in Engineering Application and Technology, 2024)
Significant environmental pollutants, volatile organic compounds (VOCs) are mostly released by industrial processes such fuel combustion, chemical synthesis, and petroleum refining. These substances pose serious threats to human health and ecosystems because they are involved in the generation of secondary organic aerosols and photochemical ozone. There is a need for more environmentally friendly alternatives to traditional VOC removal techniques because they are frequently expensive and energy-intensive. This study investigates the effectiveness of zeolite, activated carbon from rice husk, and coconut shell activated carbon as natural adsorbents for removing acetone and methylene chloride from air. The adsorption capabilities of these materials were thoroughly assessed through a series of controlled tests. Findings showed that rice husk retained great stability in acetone adsorption while zeolite demonstrated quick acetone elimination, especially at lower concentrations. The highest methylene chloride concentrations were most effective when using coconut shell. These results highlight the significance of choosing suitable adsorbents in accordance with particular VOC removal needs and offer insightful information on incorporating natural materials into air purification systems. By advancing the creation of environmentally friendly VOC mitigation techniques, the study helps to create a better atmosphere and cleaner air.